Interplay of RFX transcription factors 1, 2 and 3 in motile ciliogenesis. Issue 16 (29th July 2020) - Lemeille, Sylvain; Paschaki, Marie; Baas, Dominique; Morlé, Laurette; Duteyrat, Jean-Luc; Ait-Lounis, Aouatef; Barras, Emmanuèle; Soulavie, Fabien; Jerber, Julie; Thomas, Joëlle; Zhang, Yong; Holtzman, Michael J; et al.
Abstract: Cilia assembly is under strict transcriptional control during animal development. In vertebrates, a hierarchy of transcription factors (TFs) are involved in controlling the specification, differentiation and function of multiciliated epithelia. RFX TFs play key functions in the control of ciliogenesis in animals. Whereas only one RFX factor regulates ciliogenesis in C. elegans, several distinct RFX factors have been implicated in this process in vertebrates. However, a clear understanding of the specific and redundant functions of different RFX factors in ciliated cells remains lacking. Using RNA-seq and ChIP-seq approaches we identified genes regulated directly and indirectly by RFX1, RFX2 and RFX3 in mouse ependymal cells. We show that these three TFs have both redundant and specific functions in ependymal cells. Whereas RFX1, RFX2 and RFX3 occupy many shared genomic loci, only RFX2 and RFX3 play a prominent and redundant function in the control of motile ciliogenesis in mice. Our results provide a valuable list of candidate ciliary genes. They also reveal stunning differences between compensatory processes operating in vivo and ex vivo .